Microneedles for advanced drug delivery: a short review - Aljubouri, Noora Ali; Masheta, Dhafir (Pharmakeftiki, 2025)
Microneedles represent an innovative and minimally invasive modality for drug administration, effectively addressing the limitations of conventional techniques such as hypodermic injections and topical applications. These instruments penetrate the stratum corneum without activating nociceptive nerve endings, thereby enabling painless delivery of both low- and high-molecular-weight pharmacological agents. Fabricated from diverse materials (including polymers, metals, and ceramics), microneedles can be engineered in various forms: solid, hollow, coated, and dissolvable. Each type offers distinct advantages for systemic drug delivery and targeted localized treatments. The clinical applications of microneedles span multiple disciplines, including dermatology, vaccination, wound healing, ocular therapy, oncology, and cosmetic procedures. Despite their promise, challenges remain in material selection, drug encapsulation, and manufacturing scalability. Continued advancements in microneedle technology signal substantial potential for enhancing patient adherence, improving therapeutic precision, and reducing adverse effects. This review outlines recent developments in microneedle systems, highlighting design classifications, fabrication methods, constituent materials, and pharmaceutical applications.